Penentuan Kualitas Air di Danau Kelapa Gading Kelurahan Kisaran Naga Kabupaten Asahan Provinsi Sumatera Utara - Nathasya Zaharuddin; Hesti Wahyuningsih; Ahmad Mutadi (AQUACOASTMARINE, 2016)
Lake Kelapa Gading is an artificial lake located in Kisaran Naga district, Asahan. Through the time, Lake Kelapa Gading has been used not only as a rain shelter, but also as a tourism place and floating fish cage. The purpose of this study was to determine the status of water quality of Lake Kelapa Gading. This research used Purposive Random Sampling method by selecting five activity-based-stations on Lake Kelapa Gading. Data were analyzed by using Storet Method and Pollution Index. Water sampling is done by using a modified Van Dorn Water Sampler. The measured parameters were Physics (temperature, TSS, Brightness and conductivity), Chemistry (DO, pH, BOD, COD, Nitrate and Phosphate) and Biology (total coliform). The result of water quality status using Storet Method, based on standard class II and III, scored -30 and -7 of each. The status of water quality using pollution index method, based on class II and III, scored 2.75 and 1.53 of each. Based on the Storet Method, the status of water quality of Lake Kelapa Gading was medium-polluted, while based on the pollution index, it was low-polluted.Keywords : Kisaran, Lake, Pollution, Water Quality.